MORFOMETRIK LAMUN DI ZONA INTERTIDAL PERAIRAN PANTAI DESA ADMINISTRATIF MALAKU KECAMATAN SERAM UTARA KABUPATEN MALUKU TENGAH - Elly, Sovian Sesca; Latumainasse, Anisa; Rumengan, Yuliana; Simal, Rufiati (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Background: Seagrass is an angiosperm flowering plant that can grow well in coastal environments. Seagrass is a one seed plant that has roots, stems, rhizomes, leaves, flowers, fruit and seeds. Differences in substrate type, environmental conditions and nutrient content can influece the existence of seagrass species and their morphometric shapes.This research aims to determine the morphometric of seagrass in the intertidal zone of coastal waters of Malaku Administrative Village, North Seram Sub-district Methods: Sampling used a roaming survey method in the intertidal zone of coastal waters of Malaku Administrative Village. The research data were analyzed descriptively based on the results of species identification, observations and measurements of the segrass morphological structure. Results : The type of seagrass found in the intertidal zone of the coastal waters of the Malaku Administrative village is Cymodocea serulata, Cymodocea rotundata, Halophila ovalis, Halophila minor, Halodule pinifolia, Halodule uninervis, Thalassia hemprichii, and Syringodium isoetifolium. Morphometric forms of seagrass include : Root length ±3cm-16,5cm. Rhizome distance ±1cm–4,5cm. leaf blade length ± 2,4cm-15cm. The shape of the leaf blade is flat, oval, cylindrical, serrated at the tip of the leaf and small in length. Leaf width ±0,2cm-1cm, seagrass stand heigth ± 3-19,3cm. Conclusion: From the research results obtained, it can be concluded that the intertidal zone of the coastal wters of the malaku administrative village are 8 (eigth) types of seagrass and have morphometric structure that vary in size.